The Fourth Catalog of Active Galactic Nuclei Detected by the Fermi Large Area Telescope: Data Release 3 - Ajello, M.; Baldini, L.; Ballet, J.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Bonino, R.; Brill, A.; Bruel, P.; Buson, S.; et al. (Astrophysical Journal Supplement Series, 2022)
An incremental version of the fourth catalog of active galactic nuclei (AGNs) detected by the Fermi Large Area Telescope is presented. This version (4LAC-DR3) derives from the third data release of the 4FGL catalog based on 12 yr of E > 50 MeV gamma-ray data, where the spectral parameters, spectral energy distributions (SEDs), yearly light curves, and associations have been updated for all sources. The new reported AGNs include 587 blazar candidates and four radio galaxies. We describe the properties of the new sample and outline changes affecting the previously published one. We also introduce two new parameters in this release, namely the peak energy of the SED high-energy component and the corresponding flux. These parameters allow an assessment of the Compton dominance, the ratio of the inverse-Compton to the synchrotron-peak luminosities, without relying on X-ray data.
CRIS-Team WoS Importer:2023-01-20